2023
DOI: 10.3390/jcm12093280
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fibroblasts in Chronic Inflammatory Signalling in Chronic Rhinosinusitis with Nasal Polyps—A Systematic Review

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is an inflammatory disease of the nose and paranasal sinuses characterized by the presence of nasal polyps. The symptoms produced by the presence of nasal polyps such as nasal obstruction, nasal discharge, facial pain, headache, and loss of smell cause a worsening in the quality of life of patients. The source of the nasal polyps remains unclear, although it seems to be due to a chronic inflammation process in the sinonasal mucosa. Fibroblasts, the main cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…Increased protein levels of S100A8, S100A9, and S100A8/A9, were demonstrated in the nasal polyp tissues of CRSwNP patients compared to those in the IT tissues of controls, suggesting evident neutrophil recruitment in CRSwNP 9 . Previous studies have demonstrated that cytokines derived from epithelial cells and stromal cells facilitate neutrophilic inflammation in CRS 10,11 . Nevertheless, specific cell types that secrete these factors and drive neutrophilic inflammation in CRSwNP remain ill-defined.…”
Section: Introductionmentioning
confidence: 96%
“…Increased protein levels of S100A8, S100A9, and S100A8/A9, were demonstrated in the nasal polyp tissues of CRSwNP patients compared to those in the IT tissues of controls, suggesting evident neutrophil recruitment in CRSwNP 9 . Previous studies have demonstrated that cytokines derived from epithelial cells and stromal cells facilitate neutrophilic inflammation in CRS 10,11 . Nevertheless, specific cell types that secrete these factors and drive neutrophilic inflammation in CRSwNP remain ill-defined.…”
Section: Introductionmentioning
confidence: 96%